The influence of orthotics on pronation, impact loads and plantar pressure distribution during running - Althoff, K.; Hagen, M.; Schrooten, J. -H.; Henning, E. M. (ESM 2008 emed scientific meeting, 2008)
Orthotics are often recommended as an additional possibility to reduce excessive rearfoot motion during running. There are controversial results in the literature whether orthotics are really helpful in fulfilling this function. The purpose of this study was to examine the effect of custom made and commercially available prefabricated orthotics on pronation, impact loads and plantar pressure distribution in two different footwear conditions.